Combined liver transplant and pancreaticoduodenectomy for inflammatory hilar myofibroblastic tumor: Case report and review of the literature. (20th December 2016) - Berumen, Jennifer; McCarty, Patrick; Mo, Jun; Newton, Kimberly; Fairbanks, Timothy; Mekeel, Kristin; Hemming, Alan
Abstract: IMT, previously known as IPT, is a relatively rare tumor that was originally described in the lungs, but case reports have reported the tumor in almost every organ system. Surgical resection is typically the mainstay of therapy; however, tumors have also been shown to respond to chemotherapy or anti‐inflammatory therapy and some have spontaneously regressed. We present a literature review and case report representing the first documentation to date of liver transplant combined with PD for surgical resection of a myofibroblastic tumor non‐responsive to medical therapy.